Pendekatan Karakteristik Budaya Organisasi Dan Semangat Kerja Dalam Menyelesaikan Masalah Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Syamsudin Syamsudin; Muhamad Suhaemi; YOGA ADIYANTO (Jurnal Akuntansi Manajemen (JAKMEN), 2022)
This study aims to determine the effect of the characteristics of organizational culture and morale on employee performance with job satisfaction as an intervening variable at PT. Toyota Cilegon shoots. This research was conducted using quantitative research methods. The selection technique for the sample taken is all the population in PT. Tunas Toyota Cilegon, amounting to 95 respondents. The results showed that there was no significant influence between the characteristics of organizational culture on employee performance, there was a significant influence between morale on employee performance, there was a significant influence between job satisfaction on employee performance, there was a significant influence between the characteristics of organizational culture on satisfaction work, there is a significant influence between morale on job satisfaction, job satisfaction being the intervening variable between the characteristics of organizational culture on employee performance because the value of the indirect effect is greater than the direct effect, job satisfaction is not an intervening variable between morale on employee performance because of the influence indirect effect is not as big as the direct effect.